Management of adverse events associated with ixazomib plus lenalidomide/dexamethasone in relapsed/refractory multiple myeloma. (9th May 2017) - Kumar, Shaji; Moreau, Philippe; Hari, Parameswaran; Mateos, Maria‐Victoria; Ludwig, Heinz; Shustik, Chaim; Masszi, Tamas; Spencer, Andrew; Hájek, Roman; Romeril, Kenneth; Avivi, Irit; Liberati, Anna M.; et al.
Summary: The oral proteasome inhibitor ixazomib is approved in the United States, European Union and other countries, in combination with oral lenalidomide and dexamethasone (Rd), for the treatment of patients with multiple myeloma who have received at least one prior therapy. Approval was based on the global, randomised, double‐blind, placebo‐controlled Phase III TOURMALINE‐MM1 study of ixazomib‐Rd (IRd) versus placebo‐Rd in patients with relapsed/refractory multiple myeloma. IRd resulted in a significant improvement in progression‐free survival versus placebo‐Rd (median: 20·6 vs. 14·7 months; hazard ratio 0·74). Common toxicities observed more commonly with IRd versus placebo‐Rd were thrombocytopenia, nausea, vomiting, diarrhoea, constipation, rash, peripheral neuropathy, peripheral oedema and back pain; these were generally grade 1/2 in severity except for thrombocytopenia (19% vs. 9% grade 3/4), which appeared manageable and reversible, with no differences between arms in significant bleeding or dose discontinuations. No cumulative toxicities were observed, indicating the potential feasibility of long‐term IRd treatment. Safety data from TOURMALINE‐MM1 are reviewed and guidance for managing clinically relevant adverse events associated with IRd is provided. Most toxicities were manageable with supportive care and dose delays or reductions as needed. Clinicians should be aware of and understand these potential side effects to optimise and prolong patient benefit.